Prospek Pengembangan Cabai Rawit di Kecamatan Arut Selatan Kabupaten Kotawaringin Barat - Novi Nurhayati (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The purpose of this research is to know the analysis of chili pepper farming and the prospect of cayenne pepper development in the sub-district of Arut Selatan Kotawaringin Barat regency. Analysis of cayenne pepper includes income analysis, acceptance, revenue cost ratio, Break-even point price, break-even point production, return on investment. The prospect of chili pepper development can be known by the strengths, weaknesses, opportunities, and threats. The data needed in this study are secondary data and primary data variable cost, fixed cost, price, and quantity of production. Pursuant to result of research of cayenne pepper farm have to value of acceptance equal to Rp. 11.723.333,33., income equal to Rp. 5.618.333,33.,; revenue-cost ratio equal to 1.90; break-even point production equal to 124,14 kg; break-even point price equal to Rp. 26.038,27 and return on investment equal to 90,25%. The prospect of the development of chili pepper farm has a good prospect because based on SWOT analysis is in quadrant I which means very profitable for a business, which has the strength and the chances of mutual support.